Nutritional composition, extraction, and utilization of wheat germ oil: A review - Ghafoor, Kashif; Musa Ozcan, Mehmet; Al-Juhaimi, Fahad; Babiker, Elfadil E.; Sarker, Md. Zaidul Islam; Mohamed Ahmed, Isam A.; Ahmed, Mohammed Asif (Wiley-VCH Verla, 2017)
Wheat germ is a by-product of wheat milling from which wheat germ oil (WGO) can be obtained using different techniques. For a better quality WGO, techniques such supercritical fluid fractionation, molecular distillation, and other innovative methods can be adopted. WGO is composed of nonpolar lipids, glycolipids, phospholipids, alcohols, esters, alkene, aldehydes, tocopherols, n-alkanols, sterols, 4-methyl sterols, triterpenols, hydrocarbons, pigments, and volatile components. The most abundant WGO fatty acid is linoleic acid which composes 42–59% of total triglycerides followed by palmitic (16:0) and oleic acids (18:1). The stearic acid, a saturated fatty acid, is usually less than 2%. WGO is rich in tocopherols particularly vitamin E. It contains a-tocopherol and b-tocopherol which gives various health benefits to it. It is being used in medicine, cosmetic, agricultural, and food industry. Some of its applications include production of vitamins and food supplements, animal feed and biological insect control and for treating circulatory/cardiac disorders and weaknesses. More studies are required for producing better quality WGO such as application of more innovative and optimized techniques that can increase its health benefits and hence utilization. More mechanistic approaches for extraction, evaluation, and utilization of WGO can help in making this by-product of wheat processing more valuable.